White Students’ Perceptions of the Costs and Consequences of Being Black - Exum, Myron Lyn (Race and social problems, 2023)
Many whites explicitly believe that their race has had no impact on their accomplishments in life. The current study used the contingent valuation method to implicitly measure the value of being white—or alternatively, the cost of being black—among a sample of white college students. Participants were presented with a hypothetical scenario in which their racial appearance was altered due to a medical mishap, and then asked to identify the negative consequences they would experience as a result of this change. Participants also assigned a dollar value to their race by reporting the smallest financial settlement they would accept as compensation for the mishap. Results revealed that white students who imagined being black anticipated financial consequences significantly more often than black students who imaged being white, but they anticipated psychosocial consequences significantly less often. The median financial settlement for whiteness was relatively low, while the mean value was quite large and highlighted the importance of whiteness among certain respondents. These findings are discussed, with suggestions for future research.